Septic Shock and the Aging Process: A Molecular Comparison - Pinheiro da Silva, Fabiano; Machado, Marcel Cerqueira César (Frontiers in Immunology, 2017)
Aging is a continuous process promoted by both intrinsic and extrinsic factors that each trigger a multitude of molecular events. Increasing evidence supports a central role for inflammation in this progression. Here, we discuss how the low-grade chronic inflammation that characterizes aging is tightly interconnected with other important aspects of this process, such as DNA damage, mitochondrial dysfunction, and epigenetic changes. Similarly, inflammation also plays a critical role in many morbid conditions that affect patients who are admitted to Intensive Care. Although the inflammatory response is low-grade and persistent in healthy aging while it is acute and severe in critically ill states, we hypothesize that both situations have important interconnections. Here, we performed an extensive review of the literature to investigate this potential link. Because sepsis is the most extensively studied disease and is the leading cause of death in Critical Care, we focus our discussion on comparing the inflammatory profile of healthy older people with that of patients in septic shock to explain why we believe that both situations have synergistic effects, leading to critically ill aged patients having a worse prognosis when compared with critically ill young patients.